Spatial variability and mapping of soil fertility status in a high‑potential smallholder farming area under sub‑humid conditions in Zimbabwe - Soropa, Gabriel; Mbisva, Olton M.; Nyamangara, Justice; Nyakatawa, Ermson Z.; Nyapwere, Newton; Lark, R. Murray (Springer, 2022)
A study was conducted to examine spatial variability of soil properties related to fertility in maize felds across varying soil types in ward 10 of Hurungwe district, Zimbabwe; a smallholder farming area with sub-humid conditions and high yield potential. Purposively collected and geo-referenced soil samples were analyzed for texture, pH, soil organic carbon (OC), mineral N, bicarbonate P, and exchangeable K. Linear mixed model was used to analyze spatial variation of the data. The model allowed prediction of soil properties at unsampled sites by the empirical best linear unbiased predictor (EBLUP). Evidence for spatial dependence in the random component of the model was evaluated by calculating Akaike’s information criterion. Soil pH ranged from 4.0 to 6.9 and showed a strong spatial trend increasing from north to south, strong evidence for a diference between the home and outfelds with homefelds signifcantly higher and between soil textural classes with the sand clay loam fraction generally higher. Soil OC ranged from 0.2 to 2.02% and showed no spatial trend, but there was strong evidence for a diference between home and outfelds, with mean soil OC in homefelds signifcantly larger, and between soil textural classes, with soil OC largest in the sandy clay loams. Both soil pH and OC showed evidence for spatial dependence in the random efect, providing a basis for spatial prediction by the EBLUP, which was presented as a map. There were signifcant spatial trends in mineral N, available P and exchangeable K, all increasing from north to south; signifcant diferences between homefelds and outfelds (larger concentrations in homefelds), and diferences between the soil textural classes with larger concentrations in the sandy clay loams. However, there was no evidence for spatial dependence in the random component, so no attempt was made to map these variables. These results show how management (home felds vs outfelds), basic soil properties (texture) and other factors emerging as spatial trends infuence key soil properties that determine soil fertility in these conditions. This implies that the best management practices may vary spatially, and that site-specifc management is a desirable goal in conditions such as those which apply in Ward 10 of Hurungwe district in Zimbabwe.